The complete chloroplast genome sequence of Corylopsis multiflora Hance var. nivea Chang. Issue 1 (2nd January 2021) - Lv, Ting; Chen, Shuifei; Zhao, Rong; Wang, Ningjie; Fang, Yanming
Abstract: Corylopsis multiflora Hance var . nivea Chang is a variety of the species C . multiflora in the family Hamamelidaceae and is classed as critically endangered (CR) in the Red List of China Higher Plants. The complete chloroplast genome sequence of this taxon (as C . multiflora var. nivea in GeneBank, accession number: MW043717) was reported in this study. The genome size is 158, 993 bp in length, consisting of a pair of inverted repeat regions (IR, 26, 213bp), large single copy (LSC, 87, 895bp) and small single copy (SSC, 18, 672bp). A total of 133 genes were annotated that included 87 protein coding genes (PCGs), 37 transfer RNA (tRNAs), and 8 ribosome RNA (rRNAs) and 1 pseudo gene. GC content were 38.01%. The Bayesian phylogeny tree showed that C . multiflora var . nivea formed a monophyletic branch with Corylopis coreana and Corylopsis spicata.